Influence of increasing weights on the motor characteristics of running in track and out sprinter athletes - Gorshunova E.P.; Ogandzhanov A.L.; Pokhachevskiy A.L.; Poryadkov S.S.; Kudryashov S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the influence of increasing load on the kinematic and ergometric characteristics of sprinters when performing a specific exercise, to identify the relationship of these characteristics with the results of competitive activity. Methods and structure of the study. 16 male sprinters were examined, qualifications: I sports category - master of sports. The Optogait optical-electronic system, Witty electronic timing and Sprint 1080 traction device are used to record the ergometric and kinematic characteristics of running. Results and conclusions. Biomechanical indicators of sprinters were identified that influence the efficiency of performing a competitive exercise (tempo 5 m, 30 m, V 30 m, Acc 30 m, tk 30 m). In subjects of various sports levels, the biomechanical characteristics of running are determined to a greater extent by speed abilities (tk5m; pace 5 m) rather than by strength abilities (Acc 30 m; W/kg). Qualitative differences in fatigue make it possible to increase the objectivity of assessing the state of athletes sports form.